Effect of an Exogenous Emulsifier on Growth Performance in Weanling Pigs - Preeyaphan Udomprasert,; Theera Rukkwamsuk, (Agriculture and Natural Resources, 2006)
A trial involving 1,885 weanling pigs (24 d of age) was conducted to determine if an exogenous emulsifier, glyceryl polyethyleneglycol ricinoleate (Bredol®), would improve growth performance and prevent deterioration of fat in the diets in a three-phase starter feeding regime. Creep diet was fed from d 0 to 7, Nursery 1 diet from d 7 to 21 and Nursery 2 diet from d 21 to 35 post-weaning. Five percents of crude soybean oil were added to all diets. Bredol® was homogenized with the fat source prior to mixing with the treatment diets. Diets were mixed every other day and samples were sent to the laboratory within 2 days after mixing for determination of lipid oxidation. Lipid oxidation was measured in mg malonaldehyde per g of sample. Pigs were randomly allocated into 145 pens, each of 13 pigs. Pen was considered the experimental unit. There were 73 pens for the control group and 72 pens for the treatment group. Pigs were fed to appetite 6-8 times per day using feed trough and had ad libitum access to one waterer per pen. The body weight of each pig was recorded when moving in (weaning weight) and out of the nursery and the feed intake was recorded daily on a pen basis. The average daily gain and feed conversion ratios of pigs fed Bredol® treated diets were improved by 19.65 gm/day ( P = 0.0129) and 0.06 (P = 0.0048) respectively. Average lipid oxidations in the Bredol® treated diets measured 2 and 7 days after mixing were lower than in the control diets (P = 0.0000). These results demonstrated that addition of Bredol® to diets for weanling pigs improved growth performance and reduced deterioration of fat in the diets.